Educational Television Broadcasting in Germany: Prevailing Practices, Existing Challenges and Adoptable Policies - Pradeep Kumar Misra (FernUniversität Hagen, 2010)
Television is widely used for educational purposes but has still not achieved its fullest potential neither in developed nor in developing countries. This worldwide under performance invite experts and academics to join hands to search causes and provide suggestions to make television a better and popular learning tool. Guided by this philosophy, the present paper analyzes the educational television broadcasting in Germany from different perspectives. The focus of analysis includes measures and practices adopted by German institutions/broadcasters to promote educational television. Besides dealing with these issues, the paper discusses existing challenges and suggests best adoptable educational television broadcasting polices from Germany to promote educational television in global perspectives.